2012
DOI: 10.1530/eje-12-0632
|View full text |Cite
|
Sign up to set email alerts
|

The association of cardiac ventricular hypertrophy with congenital hyperinsulinism

Abstract: Objective: Ventricular hypertrophy (VH) has been observed in children with congenital hyperinsulinism (CHI), a condition of hypoglycaemia characterised by dysregulated insulin secretion, but the prevalence is not known. Patients and methods: Cardiac assessment was performed in children (nZ49) with CHI at diagnosis and follow-up. Two dimensional and Doppler echocardiography studies were used to assess cardiac structures, while M-mode study was used to measure left ventricular (LV) dimensions, subsequently conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This patient had a previously unreported association of ALCAPA, peripheral pulmonary artery stenosis, and congenital hyperinsulinism. Infants with congenital hyperinsulinism have been reported to have an increased incidence of cardiac structural lesions and hypertrophic cardiomyopathy , however coronary or pulmonary artery abnormalities have not been previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…This patient had a previously unreported association of ALCAPA, peripheral pulmonary artery stenosis, and congenital hyperinsulinism. Infants with congenital hyperinsulinism have been reported to have an increased incidence of cardiac structural lesions and hypertrophic cardiomyopathy , however coronary or pulmonary artery abnormalities have not been previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…24 Also, INS as a growth factor plays a role in the differentiation process of stem cells into brain and nerve cells 25, 26 The present study showed that INS is the most effective biomarker related to CHI, in line with the results of other studies. 27 In a study conducted on patients with congenital hyperinsulinism, they found that a large percentage of infants with this disease have ventricular hypertrophy, which may be related to the severity of CHI at the time of diagnosis, making the previous care of these patients even more severe. 28 The results showed that PRKACA is the second most effective biomarker related to CHI.…”
Section: L28mentioning
confidence: 99%
“…Correction of hypoglycaemia can also be complicated by the development of heart failure from exuberant dextrose containing fluid overload while attempting to maintain a high carbohydrate intake. It is well recognized that children with CHI commonly have cardiac ventricular hypertrophy, which may predispose these children to pulmonary oedema . Furthermore, oral treatment with Diazoxide, a K ATP channel opening agent, may cause fluid retention in the whole body, and sometimes specifically in the pericardial cavity, leading to acute cardiovascular compromise.…”
Section: Principles Of Clinical Management Of Chimentioning
confidence: 99%